EFEKTIVITAS PEMBELAJARAN IPS BERBASIS DIGITAL DI SEKOLAH DASAR: Kajian Etnolearning pada Tiga Sekolah Dasar di Wilayah Sumatera Barat - Olivia, Dina; Rahmadani , Elsa; Kurnia Faza , Ghefira; Fitria , Yanti; Kharisma , Inggria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research seeks to examine and depict the extent to which digital-based Social Studies (IPS) instruction is effectively carried out in three elementary schools in West Sumatra: UPT SDN 09 Sungai Aro, SDN 22 Andalas Barat, and SDN 11 Kampung Darek. A mixedmethods descriptive research design was adopted, with data gathered through ethnolearning activities that included non-participatory classroom observation, structured interviews with teachers, and questionnaire distribution to 64 fifth-grade students using a Likert scale instrument. The findings reveal that digital-based IPS learning is overall categorized as Effective, with an average percentage of 75.03%. At the individual school level, SDN 11 Kampung Darek achieved the highest rating of Very Effective (81.8%), whereas SDN 09 Sungai Aro (76.3%) and SDN 22 Andalas Barat (69.3%) were both rated Effective. The use of digital media including educational videos, visual imagery, and slide presentations demonstrably enhanced students' conceptual understanding and motivation to learn. Principal obstacles included insufficient ICT devices, frequent internet connectivity disruptions, and unequal levels of digital literacy among students. The study points to the necessity of equitable digital infrastructure development, ongoing technology competency training for teachers, and the cultivation of a collaborative digital learning culture in schools